2022
DOI: 10.1021/acs.jpclett.2c02126
|View full text |Cite
|
Sign up to set email alerts
|

Charge of Phospholipids Determines the Rate of Lysozyme Aggregation but Not the Structure and Toxicity of Amyloid Aggregates

Abstract: Biophysical properties of plasma membranes are determined by a chemical structure of phospholipids, including saturation of fatty acids and charge of polar heads of these molecules. Phospholipids not only determine fluidity and plasticity of membranes but also play an important role in abrupt aggregation of misfolded proteins. In this study, we investigate the role of the charge of the most abundant phospholipids in the plasma membrane on the aggregation properties of the lysozyme. We found that the charge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 42 publications
10
32
0
Order By: Relevance
“…Using nanoinfrared spectroscopy, also known as atomic force microscopy infrared (AFM-IR) spectroscopy, the researchers demonstrated that insulin strongly interacts with both phosphatidylcholine (PC) and cardiolipin (CL). In AFM-IR, a metallized scanning probe is placed on the sample of interest. Next, the sample is illuminated by pulsed tunable IR laser, which induces thermal expansions in the sample. These expansions are recorded by the probe and converted into IR spectra. ,, Thus, AFM-IR can be used to determine the chemical structure of individual protein aggregates. , Using AFM-IR, Rizevsky and co-workers also found that both PC and CL were found to be present in insulin oligomers that were grown in the presence of these phospholipids . Independently, Matveyenka and co-workers demonstrated that the degree of saturation of FAs of both PC and CL plays an important role in insulin aggregation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using nanoinfrared spectroscopy, also known as atomic force microscopy infrared (AFM-IR) spectroscopy, the researchers demonstrated that insulin strongly interacts with both phosphatidylcholine (PC) and cardiolipin (CL). In AFM-IR, a metallized scanning probe is placed on the sample of interest. Next, the sample is illuminated by pulsed tunable IR laser, which induces thermal expansions in the sample. These expansions are recorded by the probe and converted into IR spectra. ,, Thus, AFM-IR can be used to determine the chemical structure of individual protein aggregates. , Using AFM-IR, Rizevsky and co-workers also found that both PC and CL were found to be present in insulin oligomers that were grown in the presence of these phospholipids . Independently, Matveyenka and co-workers demonstrated that the degree of saturation of FAs of both PC and CL plays an important role in insulin aggregation .…”
Section: Introductionmentioning
confidence: 99%
“… 22 31 These expansions are recorded by the probe and converted into IR spectra. 18 , 19 , 32 35 Thus, AFM-IR can be used to determine the chemical structure of individual protein aggregates. 26 31 , 33 37 Using AFM-IR, Rizevsky and co-workers also found that both PC and CL were found to be present in insulin oligomers that were grown in the presence of these phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…Similar interactions are thought to stabilize such protein‐lipid aggregates (Alza et al, 2019; Galvagnion, 2017; Giasson et al, 2001; Kiechle et al, 2020; Ueda et al, 1993). Using nano‐Infrared spectroscopy, our group demonstrated that such aggregates possessed lipids in their structure (Zhaliazka et al, 2022; Zhaliazka & Kurouski, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings also suggest that a change in the relative concentrations of two zwitterions does not substantially alter the rate of insulin aggregation, which is consistent with the reported results for lysozyme by Zhaliazka and co-workers, according to which both PC and PE equivalently strongly inhibit protein aggregation. 44 Morphological and Structural Characterization of Insulin Aggregates Grown in the Presence of LUVs with Different Concentrations of PS. We utilized AFM to examine the morphology of insulin aggregates grown in the presence of LUVs with different concentrations of PS.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Specifically, the equimolar presence of fully saturated PS enabled the strongest enhancement of the rate of insulin aggregation compared to PS with unsaturated fatty acids. It was also found that insulin and lysozyme aggregates formed in the presence of PS exerted significantly different cell toxicities compared to the fibrils grown in the lipid-free environment. ,, Although the above-discussed findings can be valuable for the understanding of the role of PS in amyloidosis, they were obtained upon exposition of both insulin and lysozyme to the large unilamellar vesicles (LUVs) composed of PS alone. ,, The question to ask is whether an increase in the concentration of PS relative to zwitterionic lipids, such as PC and phosphatidylethanolamine (PE), primary constituents of the plasma membranes of most eucaryotic cells, would alter the rate of protein aggregation, as was evident for PS itself. To answer this question, we used a set of biophysical and molecular biology techniques that allowed for the determination of the rate of protein aggregation, the elucidation of morphology, secondary structure, and the toxicity of protein aggregates grown in the presence of lipid mixtures and in the lipid-free environment.…”
Section: Introductionmentioning
confidence: 99%